Delivery after caesarean section: review of 2176 consecutive cases. Issue 6588 (27th June 1987) - Molloy, B G; Sheil, O; Duignan, N M
Abstract : A total of 2176 consecutive patients who had had one previous caesarean section were studied retrospectively. A repeat elective caesarean section was performed in 395 (18.2%). Labour started spontaneously in 1363 patients, 301 of whom were given oxytocin to accelerate inert labour, and was induced by amniotomy and infusion of oxytocin in 418 women; 1618 of these 1781 patients (90.8%) delivered vaginally. Patients who had had a previous vaginal delivery were more likely to deliver vaginally again. Those women in whom the initial caesarean section had been performed during labour before the cervix was 4 cm dilated were less likely to deliver vaginally than those who had progressed further in labour or those who had had an elective caesarean section. Similarly, those who received oxytocin to stimulate inert labour were more likely to require a repeat caesarean section than those who did not. The uterine scar ruptured in only eight (0.45%) of the 1781 patients allowed into labour. The risk of rupture of the scar was not increased by the use of oxytocin alone either to induce or to accelerate labour. The combination of oxytocin to accelerate labour and epidural analgesia to provide pain relief, however, was associated with an increased incidence of scar rupture. Labour may be safely allowed in women who have had a previous caesarean section, most of whom will deliver vaginally. Induction of labour does not increase the risk of either a repeat caesarean section or rupture of a uterine scar.